2008
DOI: 10.1063/1.3032910
|View full text |Cite
|
Sign up to set email alerts
|

Secondary electron emission from freely supported nanowires

Abstract: We present secondary electron ͑SE͒ emission results from freely supported carbon/silicon nitride ͑Si 3 N 4 ͒ hybrid nanowires using scanning electron microscopy. We found that, contrary to bulk materials, the SE emission from insulating or electrically isolated metallic nanowires is strongly suppressed by the penetrating beam. A mechanism of the SE suppression by the positive specimen charging is proposed, which is based on a total emission yield calculation using the Monte Carlo technique. This finding provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In a process that involves electron-beam (EB) imaging, the scattering of electrons in materials associated with the imaging process determines the secondary electron emission coefficient (SEEC), 1,2 image resolution, 2,3 image contrast, 3,4 pattern profile, 5 and many other such image characteristics. Especially for a 3-D stack structure, the incident beam energy, varying from 0.1 to 30 keV, greatly influenced the electron imaging characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In a process that involves electron-beam (EB) imaging, the scattering of electrons in materials associated with the imaging process determines the secondary electron emission coefficient (SEEC), 1,2 image resolution, 2,3 image contrast, 3,4 pattern profile, 5 and many other such image characteristics. Especially for a 3-D stack structure, the incident beam energy, varying from 0.1 to 30 keV, greatly influenced the electron imaging characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…To study these observed phenomena quantitatively, we simulate the SE generation using the Monte Carlo method. In our previous studies, 29,30 we have developed Monte Carlo simulation codes to simulate the scattering process of PEs in the carbon specimen and the generation of SEs. In the codes, Mott cross-sections are implemented for elastic scattering and a continuously slowing-down approximation is assumed for averaged inelastic processes.…”
Section: Discussionmentioning
confidence: 99%
“…The SEs are the electrons emitted from material surface, including true secondary electrons (TSEs) and backscattering secondary electrons (BSEs). [9] Those TSEs are generated by inelastic scattering events between incident electrons and material extra-nuclear electrons, while elastic scattering events between incident electrons and material nuclei may result in BSEs. [10] Yield of SE due to electron irradiation can be calculated with both Monte Carlo (MC) numerical simulations and formulas directly.…”
Section: Introductionmentioning
confidence: 99%